Struggling to build an alternative to Assad: Structural flaws and lack of protection undermine Syria's opposition government - Khaled Yacoub Oweis (Stiftung Wissenschaft und Politik (SWP), 2014)
International powers backing the Syrian opposition are turning their attention to an Interim Government founded in November 2013. The February 2014 collapse of the Geneva peace talks, which were supposed to produce a political transition, and growing alarm over chaos in rebel areas and gains by hard-line Islamists, have prompted renewed efforts to help the opposition fill the vacuum left by the collapse of central authority in large parts of Syria. Yet, the new entity has had little impact on the ground. Nor does the sacking of its first prime minister after only months bode well for its independence. In addition, regime strikes, opposition infighting, and a fundamental lack of security will lead to failure unless the opposition is revamped and a military umbrella created to allow it to govern inside Syria. (SWP Comments)
Keywords: 320